The Digital Story of Science: Experiences of Pre-Service Science Teachers - Munise Seckin-Kapucu; Zeynep Yurtseven-Avci (Journal of Education in Science, Environment and Health)
The purpose of the study is examination of the quality of digital stories developed by pre-service science teachers and deeply investigating pre-service teachers’ experiences related to scientific concepts, the characteristics of scientific knowledge and the ways of reaching scientific knowledge in the stages of exploration, storytelling and digitalization. A case study design is used in the research. Criterion sampling was used from the purposeful sampling methods. The research was carried out with the 3th year 36 pre-service teachers who study at a public university in Turkey during the fall semester of 2018-2019. Rubric for Evaluation of Digital Stories, semi-structured reflection form and digital diaries form developed by researchers were used for data collection. Content analysis technique was applied to analyze the reflections and dairies, and the digital stories prepared by the participants were evaluated using the Digital Storytelling in Educational Context Rubric (DSECR) form. According to the findings, most of the digital stories prepared by pre-service science teachers were at high quality level. Participants stated that they used scientific concepts in their digital stories and transferred the characteristics of scientific knowledge to digital environment and scenarios. Additionally, science teachers' experience of preparing digital stories supported 21st century skills.